Mathematics for Multimedia - Wickerhauser, Mladen Victor; SpringerLink (Online service) (Boston : Birkhäuser Boston, 2010)
This concise textbook presents the mathematics that is foundational to multimedia applications. Featuring a rigorous survey of selected results from algebra and analysis, the work examines tools used to create application software for multimedia signal processing and communication. Key features include: * Over 100 exercises with complete solutions; * Useful algorithms presented in pseudocode and Standard C to help readers with programming, experimentation, and the solution of exercises; * Numerous illustrations based on data from real studies; * Suggestions for further reading at the end of each chapter; * A companion website maintained by the author providing computer programs described in the book as well as additional references and data files, such as images and sounds, to enhance the reader s understanding of key topics; * A supplementary manual containing several hundred exercises, solutions, and sample programs not included in the book available to instructors upon request; * Minimal prerequisites only an undergraduate-level knowledge of mathematics, not including statistics, is required. Mathematics for Multimedia is an ideal textbook for upper undergraduate and beginning graduate students in pure and applied mathematics, engineering, and computer science seeking an innovative approach to contemporary mathematics with practical applications. The work may also serve as a useful reference for multimedia applications developers and other researchers and practitioners interested in the mathematics underlying multimedia software design and implementation.
Numbers and Arithmetic -- Space and Linearity -- Time and Frequency -- Sampling and Estimation -- Scale and Resolution -- Redundancy and Information -- Answers -- Basics, Technicalities, and Digressions.
Keywords: Mathematics; Multimedia systems; Fourier analysis; Algorithms; Computer software; Mathematics; Applications of Mathematics; Multimedia Information Systems; Algorithms; Fourier Analysis; Mathematical Software